Εφαρμογή της θεωρίας παιγνίων στην ανάλυση της ροής δικύκλων σε αστικές αρτηρίες - Κουλατζίδης, Βασίλειος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών, 2016)
The main goal of this thesis is the investigation of the applicability of Game Theory in modeling the overtaking maneuver that is performed by motorcycles. Primarily, it is assumed that both the PTW driver and the driver of the vehicle being overtaken are rational decision-makers who develop strategies, while commuting in urban environment, trying to maximize their payoff depending on their decisions. A database, consisting of 850 overtaking cases, is being used in order to decide which variables better describe the decisions and the payoffs of the players who interact. As a result, four different games are constructed. For every game, we calculate the payoffs for each player using the data from the sample. Each game has different assumptions regarding the strategies that players have at their disposal, as well as the way these strategies are being quantified using real data. Respectively, in each model proposed, the payoffs and the way they are calculated are differentiated. A common characteristic that all games share is the fact that in each of them, at least one player has the strategy «Cooperate» in his set of possible actions. Results lead to the conclusion that the players participating in the game maximize their payoffs by cooperating with each other, although this situation doesn’t always appear in the real data.